Examination of Calcium Oxalate Crystals In Mountain Water Consumers In Kuningan Regency - Al Sas, Oktafirani; Prambudi, Hery; Syafitri, Mutiara (Jurnal Health Sains, 2024)
Urine, a byproduct of metabolism occurring in the kidneys, serves as a crucial diagnostic medium in laboratory settings, including the microscopic examination of calcium oxalate crystals. Influenced by various factors, such as demographics and environmental conditions, the formation of these crystals underscores broader health considerations. Mountain water, renowned for its mineral content, constitutes a significant source of daily hydration. However, the dominance of calcium and magnesium elements in surface water raises concerns regarding calcium oxalate crystallization. This study investigates the prevalence of calcium oxalate crystals in mountain water consumers within Kuningan Regency. Employing descriptive research methods and random sampling techniques, the study examined urine samples from 38 individuals. Results revealed calcium oxalate crystals in 11 participants, constituting 28.95% of the sample. This finding underscores the need for further research into water quality and its implications for public health in the region. By elucidating the relationship between water composition and urinary crystal formation, this study informs strategies for safeguarding community health and informs future policy initiatives regarding water resource management.